MANAJEMEN PENDIDIKAN KARAKTER DAN MUTU LULUSAN: STUDI SDN 1 DAN SDN 2 BUMI NABUNG UTARA, LAMPUNG TENGAH - Vani Novianto (Universitas Muhammadiyah Metro, 2026)
This study seeks to examine and delineate: the notion of educational quality shaped by the integration of character values, a framework for the planning, execution, and oversight of character education that enhances graduate quality, and the ramifications of the character education management model for elevating graduate outcomes at SDN 1 Bumi Nabung Utara and SDN 2 Bumi Nabung Utara. The study utilizes a qualitative methodology using a case study approach. Data were gathered by comprehensive interviews, participant observation, and documentation. The analysis of data employed an interactive approach comprising data gathering, data reduction, data presentation, and conclusion formulation. The results suggest that character-based educational quality is defined as the ongoing reinforcement of moral principles, behavioral discipline, and attitudinal development included into all school activities. The implementation methodology comprises habitualization, personification, role modeling, and the integration of extracurricular, intra-curricular, and co-curricular activities, as well as the establishment of a conducive learning environment. The ramifications for school policy include the creation of a character-driven curriculum, the development of regulations that govern the habituation process, and the identification of character objectives. A systemic-integrative character education management system fosters the development of graduates who exhibit academic integrity and embody exemplary character values.